2008 IEEE International Symposium on Electronics and the Environment 2008
DOI: 10.1109/isee.2008.4562920
|View full text |Cite
|
Sign up to set email alerts
|

Assessing user behaviour for changes in the design of energy using domestic products

Abstract: This paper explores the contribution that user behaviour could make to the creation of new energy efficient products. It does this by first looking at the energy demand of 6 households then discusses the identification of the products with the highest potential for improvement. This is then narrowed down to products with a high energy impact and those where a high level of human interaction and use is also evident. A model for guiding design changes based on a theoretical minimum energy level for each product … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 9 publications
(9 reference statements)
0
16
0
Order By: Relevance
“…Designers are in a position to reduce use impacts by purposefully shaping behaviour towards more sustainable practices (Lockton et al, 2008, Elias et al, 2008, Bhamra et al, 2008, Wever et al, 2008. Early research identified Eco-feedback (McCalley and Midden, 2006), Behaviour Steering (Jelsma and Knot, 2002, Akrich, 1992 and Persuasive Technology or Captology (Fogg, 2003) as potential strategies which could be integrated into product design to influence user behaviour (Lilley.…”
Section: Abstract: User Behaviour Environmental Design Design Technmentioning
confidence: 99%
See 1 more Smart Citation
“…Designers are in a position to reduce use impacts by purposefully shaping behaviour towards more sustainable practices (Lockton et al, 2008, Elias et al, 2008, Bhamra et al, 2008, Wever et al, 2008. Early research identified Eco-feedback (McCalley and Midden, 2006), Behaviour Steering (Jelsma and Knot, 2002, Akrich, 1992 and Persuasive Technology or Captology (Fogg, 2003) as potential strategies which could be integrated into product design to influence user behaviour (Lilley.…”
Section: Abstract: User Behaviour Environmental Design Design Technmentioning
confidence: 99%
“…Influencing user behaviour can be challenging. In spite of over a decade of campaigns exhorting consumers to behave differently and greater product efficiency, consumers are slow to adopt more sustainable behaviours (DeVries, 2006, Siegle, 2006 and behavioural changes made are often short-lived (Scott, 2004).Designers are in a position to reduce use impacts by purposefully shaping behaviour towards more sustainable practices (Lockton et al, 2008, Elias et al, 2008, Bhamra et al, 2008, Wever et al, 2008. Early research identified Eco-feedback (McCalley and Midden, 2006), Behaviour Steering (Jelsma and Knot, 2002, Akrich, 1992 and Persuasive Technology or Captology (Fogg, 2003) as potential strategies which could be integrated into product design to influence user behaviour (Lilley.…”
mentioning
confidence: 99%
“…As with many student design projects, the outcomes from the activities reported in this paper were not taken through to a user testing phase and as such it was not possible to determine whether the resulting designs were successful in encouraging behaviour modification. However, it is evident that this approach is gaining recognition as a subject worthy of academic study (Lockton et al, 2008;Elias et al, 2008;Design and Behaviour, 2008) and, judging by the marked increase in 'behaviour changing' products on the market (DIy Kyoto, 2005;Product Creation Ltd, 2007;Nissan Global, 2008), it is increasingly of great interest to manufacturers as well.…”
Section: Discussionmentioning
confidence: 99%
“…One user observation study demonstrated that people who perform their daily activities with a high level of interaction with kitchen appliances, sometimes cause unnecessary energy usage [13].…”
Section: Introductionmentioning
confidence: 99%